Cytokinetics study on MCF-7 cells treated with commercial and recombinant bromelain - Fouz, Nour; Amid, Azura; Hashim, Yumi Zuhanis Has-Yun (Asian Pacific Organization for Cancer Prevention, 2014)
Background: Breast cancer is the leading main cause of death in women. The available chemotherapy drugs have been associated with many side effects on cancer patients. Bromelain has a novel medicinal quality includes anti-inflammatory, anti-thrombotic, fibrinolytic and anti-cancer functions. Available commercial bromelain is obtained through tedious methods; therefore, recombinant bromelain gave cheaper and simpler choice with similar quality. Materials and Methods: This study aims to observe the effects of commercial and recombinant bromelain on the cytokinetics behavior of MCF-7 breast cancer cells and observe their potential as therapeutic alternative in cancer treatment. Cytotoxic activities of commercial and recombinant bromelain were determined using (sulforhodamine) SRB assay. Next, cell viability assay was engaged to observe the effects of commercial and recombinant bromelain on MCF-7 cells cytokinetics behavior. Finally, the established growth kinetic data was used to modify a model that predicts the effects of commercial and recombinant bromelain on MCF-7 cells. Results: Commercial and recombinant bromelain gave strong effects towards decreasing the cell viability of MCF-7 cells with IC50 value of 5.125 μg/mL and 6.25 μg/mL, respectively, compared to taxol with IC50 value of 0.063 μg/mL. The present results indicate that commercial and recombinant bromelain proved its anti-proliferative activity when they reduced the number of cells generations from 3.92 generations to 2.81 for commercial bromelain and 2.86 generations for recombinant bromelain, respectively. Observation under microscope on bromelain-treated MCF-7 demonstrated detachment experience. While taxol reduced the number of cells generations of MCF- 7 from 3.92 generations to 3.12. The inhibition activities obviously can be verified when the growth rate was decreased dynamically from 0.009 h-1 to 0.0059 h-1 for commercial bromelain and from 0.009 h-1 to 0.0063 h-1 for recombinant bromelain, respectively. Conclusions: Commercial and recombinant bromelain affect cytokinetics of MCF-7 cells by decreasing the cells viability and demonstrated similar strength as Taxol (p<0.05).